Utilización del Cuestionario General de Salud de Goldberg (GHQ-28) en la detección de los problemas psicosociales en la consulta del médico de familia - de la Revilla Ahumada, L. (Aten Primaria, 2004)
OBJECTIVE: To analyze the usefulness of the 28-item Goldberg General Health Questionnaire (GHQ-28) in identifying psychosocial problems, and to determine how the questionnaire scores are related to stressful life events (SLE), use of health services, and individual variables (age, sex, employment status, socioeconomic group, and educational level) DESIGN: Cross-sectional study. SETTING: Almanjayar Health Center in the city of Granada, Southern Spain PARTICIPANTS: 314 patients more than 18 years of age, selected by systematic sampling at an on-demand health center MAIN MEASURES: Each patient completed the GHQ-28 during the course of a personal interview, and scores of 8 or higher were considered to indicate psychosocial problems. Score on the Social Readjustment Rating Scale of Holmes and Rahe (stressful life events during the previous year) was also recorded, as were socioeconomic group, educational level, employment status and use of services (number of visits to the doctor during the previous year). All variables were subjected to descriptive analysis and their associations with the GHQ-28 score were tested with the chi-squared test. Multivariate analysis was used to identify categories that showed an independent association with highscores on the GHQ-28 RESULTS: The variables associated with a greater likelihood of psychosocial problems were female sex (OR, 2.15; CI, 1.14–4.04) and high levels of stress (OR, 2.65; CI, 1.50– 4.68). Both showed a statistically significant association with the GHQ-28 score after multivariate analysis CONCLUSIONS: The GHQ-28 is a potentially useful instrument to detect psychosocial problems in the family physician's office, and can aid in the subsequent identification andqualitative evaluation of patients